2018
DOI: 10.32601/ejal.460635
|View full text |Cite
|
Sign up to set email alerts
|

Genre-Based Approach to Writing Instruction for Students at an English Language and Literature Department

Abstract: The aim of the genre-based pedagogy is to focus on students' academic needs and enable them to read and write successfully (Martin, 1993, 2009). Therefore, it is imperative for teachers to understand the range of written genres and other writing skills that students need to use in their academic studies. This study has aimed to design an alternative and effective way of teaching writing to English Language and Literature students within the genre-based pedagogy considering their academic needs. The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 23 publications
2
10
0
1
Order By: Relevance
“…Findings revealed that not only did students' writing performance improve but their attitudes toward writing also changed. Students showed more self-confidence and positive attitudes toward writing, and their essay scores increased (Almacıoğlu & Okan, 2018). Similar results were also found in Thailand, where the TLC was applied to support the development of writing competence of 44 Thai university students.…”
Section: Genre-based Approach and The Tlcsupporting
confidence: 77%
See 1 more Smart Citation
“…Findings revealed that not only did students' writing performance improve but their attitudes toward writing also changed. Students showed more self-confidence and positive attitudes toward writing, and their essay scores increased (Almacıoğlu & Okan, 2018). Similar results were also found in Thailand, where the TLC was applied to support the development of writing competence of 44 Thai university students.…”
Section: Genre-based Approach and The Tlcsupporting
confidence: 77%
“…Genre-based approaches emphasize that writing pedagogies should provide students with explicit and systematic explanations of how language works in social contexts (Hyland, 2003;Martin, 2009;Rusinovci, 2015). Additionally, they help to improve students' ability to understand and produce texts (Almacıoğlu & Okan, 2018;Luu, 2011) in a cohesive and purposeful manner (Luu, 2011). One approach within genre-based pedagogies is informed by systemic-functional linguistics (SFL), which is the one we address in this article.…”
mentioning
confidence: 99%
“…It is a requirement to implement students centered teaching activities since writing is a process. In addition, the Genre-based approach (GBA), which is capable of being utilized since it concentrates on the generic structure of the text throughout the stage of modeling text (MoT), can be utilized [39], [40]. Teachers provide students with examples of texts to examine the social function, generic structures, and language features during the MoT stage.…”
Section: Excerptmentioning
confidence: 99%
“…In another case study, Almacıoğlu and Okan (2018) highlighted the process of building metacognitive genre awareness and influencing ELLs in the English language and literature department to compose and interpret academic text professionally. The study results showed that the participants' writing ability improved and that they acquired a metacognitive awareness, at least in the declarative type of writing.…”
Section: │ 119mentioning
confidence: 99%